Bare life at the European borders. Entanglements of technology, society and nature. Issue 2 (2nd April 2016) - Schindel, Estela
ABSTRACT: The sophisticated technology deployed for border control and surveillance at the EU borders poses a sharp contrast to the main causes for the deaths occurring in border areas, mainly due to abandonment to the elements. However, it is precisely the technology deployed at the borders which paradoxically pushes illegalized travelers to zones of greater exposure to "nature." The article explores from a cultural-sociological perspective the new configurations of technology, "culture, " and "nature" that are emerging through the EU border regime. Drawing on Agamben's category of bare life, it claims that illegalized travelers are displaced into a sphere of mere biological survival. A content and discourse analysis of the narratives attached to technological products developed for border surveillance and control reveals a symbolical construction of the illegalized traveler as contiguous to "nature" while technology is depicted as if deprived of agency. Technology and nature are often perceived as neutral, ahistorical, and value-free, but are always socially and historically constructed. This construction expresses a certain understanding of the border scenario and an underlying definition of what is "human." The paradox between the humanitarian and the securitization paradigms is thus only apparent: both rely on the construction of the illegalized travelers as bare life. A global biopolitical schism along the boundary between "nature" and "culture"—analogous to what Latour called the "great divide" between "moderns" and "others"—is being reproduced but also disputed and negotiated along the EU borders.